THE The Development Of Structured Drilling Method (Sdm) & Table Tenses Sederhana (Tts) In English Business Correspondence Classes (A Case Study In Polytechnic Of Lp3i Jakarta): (A Case Study in Polytechnic of LP3I Jakarta) - Prihandono Kuntadi; Susi Oktafiani; Mardiana, Diand (JOLADU: Journal of Language Education, 2024)
Business correspondence is a main skill of business administration students. In globalization era, when the interaction among business actors is getting intents and wider. Ability at communicating in English is totally needed. As the widest international language in international relationship, mastering English becomes a great significant fundament. The research is focused on the development of structured drilling method (SDM) which is combined to the application of Tabel Tenses Sederhana (TTS). Tabel Tenses Sederhana is a teaching aid which we can use it as a guidance for drilling students. The drilling we mean can be used both for speaking and writing activities. SDM is a drilling method which is structured and gradual based on sentence structure and vocabulary needed. The drilling is given based on lesson, material and purpose of the English training. By using various vocabulary, SDM will be able to be used for every various training purpose, starting from general English to English for specific purpose. In this research, the drilling method will be focused on potential sentences/utterance in writing business English letter. The drilling method used on SDM is a various and systematic drilling method. The application of SDM which is developed on this research will be tested in several classes of Polytechnic LP3I Jakarta.  It is needed to analyzed the effectiveness of the method and to figure out the feedback from the students. The research will be designed as qualitative research. The feedback we mean is students’ perception about the applying of TTS and SDM on English business correspondence training.